Biomaterials - Migonney, Veronique (Bioengineering and health science series., 2014)
"Discovered in the 20th century, biomaterials have contributed to many of the incredible scientific and technological advancements made in recent decades. This book introduces and details the tenets of biomaterials, their relevance in a various fields, practical applications of their products, and potential advancements of the years to come. A comprehensive resource, the text covers the reasons that certain properties of biomaterials contribute to specific applications, and students and researchers will appreciate this exhaustive textbook"--Publisher's description.